Connecting supplier and DoD blockchains for transparent part tracking - Francis Asuncion (Elsevier, 2021)
Blockchains have been around for more than ten years, and since 2015, a plethora of systems have been launched to target more flexible use cases. More recently, several enterprise blockchain systems, such as Consensys Quorum and Hyperledger Fabric, have been launched to make blockchain simpler to apply in complex organizational configurations. In this paper, we identify a specific Department of Defense use case, extrapolate requirements, and perform a thorough assessment of the different layers of the blockchain stack to identify the existing state of the art and undertake a gap analysis of the technology for this context. We describe a platform that meets many of these challenges and show how we architected, designed, and implemented a solution for this use case for deployment at NAVAIR. This solution connects transactions from two separate blockchain systems, Consensys Quorum and Hyperledger Fabric, by using a graph-based approach that preserves privacy while enabling full transparency across the military and supplier networks.